Sergei Vladimirovich Myasoyedov - A. I. Ryzhov; G. I. Mendrina; S. V. Logvinov (Бюллетень сибирской медицины, 2006)
The biography and main directions of scientific activity of professor, chief of histology and emdryology chair of the Tomsk university (since 1931 TMI) S.V. Myasoyedov are presented. Recollections of the his contemporaries and pupils are given. Historical role of S.V. Myasoyedov in the formation of science is defined.